2019
DOI: 10.4103/apjon.apjon_13_19
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Depressive Symptoms and Demographic-Medical Characteristics among Elder People with Cancer

Abstract: Objective: Cancer is one of the most common life-threatening diseases and a great source of stress in patients. The risk factors of depression differ in elder people compared to other age groups. The present study was designed to determine the relationship between depressive symptoms and demographic-medical characteristics among elder people with cancer. Methods: This cross-sectional correlational study recruited 200 elder people with cancer. The eligible patients compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
1
12
0
10
Order By: Relevance
“…Oserowsky et al [46] also found that being married was inversely associated with a positive depression screening. The results presented by Ladaninejad et al [37] partially corroborated those mentioned above, that is, higher depression scores were observed among widowed patients, while lower scores were more common among single patients.…”
Section: Sociodemographic Factors and Distresssupporting
confidence: 72%
See 3 more Smart Citations
“…Oserowsky et al [46] also found that being married was inversely associated with a positive depression screening. The results presented by Ladaninejad et al [37] partially corroborated those mentioned above, that is, higher depression scores were observed among widowed patients, while lower scores were more common among single patients.…”
Section: Sociodemographic Factors and Distresssupporting
confidence: 72%
“…The type of cancer present in each sample was highly variable, with some studies selecting people with a specific diagnosis: hematological [ 28 ], gynecologic [ 30 ], non-Hodgkin´s lymphoma [ 26 ], colorectal [ 41 ], gastrointinal [ 45 ], and bladder [ 46 ]; and others including any type of cancer [ 27 , 29 , 32 , 33 , 34 , 37 , 38 , 39 , 40 , 42 , 43 , 44 ]. Despite this variability, breast/gynecological, gastrointestinal, and colorectal cancers were the most represented, with 20.9%, 17.7% and 16.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scale contains 12 items evaluating three dimensions of support: family (including parents, children, and spouse [items 3, 4, 8, and 11]); friends (items 6, 7, 9, and 12); and other important relations (including neighbors and doctors [items 1, 2, 5, and 10]). Each item was scored on a 5-point scale ranging from 1 (strongly disagree) to 5 (strongly agree), with the total score ranging from 12 to 60 [ 63 ]. A higher score indicates better overall social support.…”
Section: Methodsmentioning
confidence: 99%